0333 Night shift work and breast cancer risk: a combined analysis of population-based case-control studies with complete work histories. (21st August 2017) - Cordina-Duverger, Emilie; Menegaux, Florence; Nambiema, Aboubakari; Rabstein, Sylvia; Harth, Volker; Pesch, Beate; Brüning, Thomas; Fritschi, Lin; Glass, Deborah; Heyworth, Jane; Erren, Thomas; Castaño-Vinyals, Gemma; et al.
Abstract : In 2007, IARC classified "shift work that involves circadian disruption" as probably carcinogenic to humans. To date, the evidence that night shift work increases the risk of breast cancer remains limited, partly because exposure to night work is defined differently across studies. To overcome this limitation, we created a single harmonised dataset using a common definition of night work from 5 major population-based case-control studies on breast cancer in Australia, Canada, France, Germany, and Spain. The dataset included 6000 breast cancer cases and 7000 population controls. Any job held during work history that included at least 3 hours between midnight and 5 am was classified as night work. Lifetime duration of night work, frequency (nights/week), and night shift length (hours) were used as the main exposure variables. In pre-menopausal women who ever worked at night the pooled OR was 1.23 [1.03–1.47]. The OR increased to 1.75 [1.17–2.62] in premenopausal women who worked at least 3 nights/week and 1.33 [1.05–1.70] for night shifts≥10 hours. The OR did not increase with the number of years of night work, but women who worked ≥3 nights/week for ≥10 years had an OR of 2.58 [1.05–6.36]. No association emerged from the data in post-menopausal women. No statistically significant heterogeneity between studies was observed. Our results support the hypothesis that night work increases breast cancer risk, particularly in pre-menopausal who worked at least 3 nights per week. The absence of an association in post-menopausal women needs further scrutiny.